El desarrollo de la oralidad en niños del nivel educativo de básica primaria (2016)
This monograph about compilation, is a qualitative research and descriptive design which aims to realize the importance of development and consolidation of oral skills in school, specifically in the educational level of primary basic; education: This through of collection and analysis of information which are toke as reference national and international studies in witch , the authors delve through research about the development of orality within the pedagogical teaching and learning processes; taking as reference the theoretical approaches about orality proposed by Walter Ong and the importance of environment in the development of language, based on the proposel of Lev Vygotsky and about the relationship between thought and language.